Suicide in the Hungarian Kingdom - Lajos Baĺint (Hungarian Demographic Research Institute, 2016)
This paper tests the theses of Durkheim's classical work (Suicide) and those of other early sociological theories by analysing district-level data of the Hungarian Kingdom at the beginning of the 20th century. So far, there have been few attempts of analysing spatial and historical suicide data for Hungary so far. Previous studies, based on qualitative sources, parish registers or using the literature of the period as a historical source, lacked the opportunities afforded by statistical analysis. The analysis of the Hungarian Kingdom has proven to be a rewarding exercise and made it possible to raise questions that thus far have received little attention in the scientific community.~ Spatial analysis makes it clear that - in contrast to the widespread opinion - not only the Great Plain can be regarded as particularly prone to high suicide rates but some regions in Transylvania were also characterised by a high frequency of suicide. The results of the spatial models generally verified Durkheim's propositions. Both basic types of suicide in the Durkheimian theory, egoist and anomie-type suicides, were found to be crucial in explaining the spatial differences of suicide in the Hungarian Kingdom. All indicators referring to social change (e.g. the share of industrial workers, divorce rate) increased the probability of suicide, whereas variables signalling strong traditional community ties or high levels of integration diminished it.~ However, as opposed to Durkheim's theory, spatial and ethnic factors were found to be more important. The concept of the imitative character of suicide or the role of adaptation to (or acceptance of) this kind of behaviour in its spatial spread proved to be important in better understanding the mechanisms of suicide.~ The ethno-linguistic variables highlighted the influence of cultural-normative factors among the driving forces of suicide. Durkheim clearly rejected the influence of ethnicity in suicide; whereas this study attributed a shared suicide culture to linguistic groups.
Keywords: I30; 300; Historical demography; Suicide